2022
DOI: 10.3390/ijerph19127543
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Colorectal Polyps in Middle-Aged and Elderly Populations

Abstract: Colorectal polyps are the precursor lesions of most colorectal cancers. This study aimed to evaluate associations between bone mineral density (BMD), metabolic syndrome (MetS), and gastrointestinal diseases with colorectal polyps in middle-aged and elderly populations. A retrospective cross-sectional study was performed using data from the health examination database of a tertiary medical center in southern Taiwan in 2015. Subjects aged 50 years and older who had been assessed for metabolic factors and had und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…In other words, it may imply a higher risk of CRC for those in the MetS group. A recent study showed that, MetS is a independent risk factor associated with colorectal polyps in the middle-aged and elderly Taiwanese population [42]. Therefore, the relapse of intestinal polyps caused by MetS is most likely the reason for the number of older people in the MetS group.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, it may imply a higher risk of CRC for those in the MetS group. A recent study showed that, MetS is a independent risk factor associated with colorectal polyps in the middle-aged and elderly Taiwanese population [42]. Therefore, the relapse of intestinal polyps caused by MetS is most likely the reason for the number of older people in the MetS group.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric fundus gland polyps are the main components of gastric polyps, most of which are manifestations of long-term proton pump inhibitor treatments [ 3 ]. Reporting the opposite of this situation, Loke et al reported that the incidence of gastric polyps in the groups of patients over 50 years of age with and without colorectal polyps was found to be statistically insignificant [ 31 ]. Therefore, some studies suggest that the etiology of positive relationships may be related to the decrease in the stomach acid barrier [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 Besides, elevated serum total cholesterol was reported to be an independent risk factor for colorectal polyps in the Taiwanese population aged 50 years and older. 7 However, other essential nutrients, such as minerals and vitamins in eggs may exert protective effects. According to the analysis from 3 large prospective studies, higher dietary vitamin D intake could lower the risk of precursor lesions for CRC and higher calcium intake could reduce the risk of conventional adenomas.…”
Section: Introductionmentioning
confidence: 99%